Interviewology : the new science of interviewing - Papalia, Anna (Harper Business, an imprint of HarperCollins Publishers, 2024)
"A guide to mastering the job interview, offering proven advice and techniques to discover your unique interview style that is key to interviewing better-for those on either side of the table"--